COMPARATIVE ANALYSIS OF ANGLO-AMERICAN AND CONTINENTAL MODELS OF JUDICIAL INVESTIGATION INVOLVING THE JURY - V. Bertovskiy, Lev; A. Lutcenko, Pavel; V. Maslov, Igor; A. Sinitsyn, Valentin; A. Nichiporenko, Alexander (Revista Gênero e Interdisciplinaridade, 2020)
The article is devoted to the analysis of experience of Anglo-American and continental legal system countries as to including the public into administration of justice as jurors. The studied form of criminal legal procedure is one of the most disputable, as it is dependent not only and not as much on the criminal-procedural legislation development, as on the condition of judicial system, its efficiency, democratization and humanization of criminal justice. Besides, the jury trial institution has not only legal but also social significance, because it is a form of the public control over observance of criminal law serving as a guarantee against abuse on the part of the state. The research objective is to comprehensively analyze the features of judicial investigation with participation of jurors in the Anglo-American and continental legal system countries, to reveal the positive experience, and to evaluate the possibility of its implementation in the Russian legal framework taking into account the dynamics of criminal-procedural legislation development. The leading research method is comparative-legal method used for studying the foreign legislation regulating the order of judicial investigation with participation of jurors. Analysis of the data on complicated form of judicial investigation is based on statistical method, and analyzing 32 criminal cases investigated by jury trial. It was concluded that the Russian model of judicial investigation with the jurors significantly differs from the foreign analogs; given the significant differences of the subject and structure, it can be defined as a composite one, combining the features of Anglo-American and continental law models. The article materials may serve as a basis for constructive academic discussion, for further insights into the issues of implementation of the citizens’ constitutional right for administering justice, and for elaboration of practical recommendations on implementation of Article 42 of the Russian Criminal-Procedural Code and clarification of certain normative provisions.